MENINGKATKAN MINAT BACA KANAK-KANAK DENGAN STRATEGI PERPUSTAKAAN KELILING DAN POJOK BACA DI DESA AIK DEWA - Jurman, Eduardus; Jurnal Wicara; Kirana, Ira Chandra; Astuty, Elyana; Putri, Baiq Sri Wulan; Hilali, Aisya Niswatul; Kurniawan, Ahmad Rizki; Prasetia, Ade; Yajnayanti, Aini Lutfia; Hairi, M. Anas; Rahmawati, Rini (Jurnal Wicara, 2025)
Limited access to reading materials in remote areas has led to the emergence of mobile library services and reading corners. The existence of these two services is strongly believed to influence the reading interest of elementary school students. This study analyzes the influence of these two strategies. The purpose of this study is to analyze the influence of mobile library services and reading corners on the reading interest of elementary school students in Aik Dewa Village, East Lombok Regency. The method used is a quantitative approach with a descriptive-verificative type. The research sample consisted of 30 students selected using purposive sampling. The data collection instrument was a questionnaire with a Likert scale (1–5) containing indicators of accessibility, collection variety, and service quality in mobile libraries; aspects of comfort, affordability, and collection quality in reading corners; and indicators of frequency, motivation, and enjoyment of reading as a representation of the reading interest variable. Based on data analysis, both variables were proven to have a significant and positive effect on reading interest. The contribution of reading corners (β=0.42) was greater than that of mobile libraries (β=0.35). The coefficient of determination (R²) of 0.679 indicates that 67.9% of the variation in reading interest can be explained by these two services. These findings confirm that the combination of strategies in the form of providing mobile libraries and reading corners is effective in increasing students' reading interest, with reading corners having a greater impact.